Judiciaries in comparative perspective - Lee, H. P., 1947- (Cambridge University Press, 2011)
"The study of judicial independence is important in national legal systems as it is an essential guarantee for democracy and liberty. Judicial independence is also an essential feature in ensuring a globalised economy. Corporations must have confidence in the impartiality and independence of the tribunals that will adjudicate disputes in the multiple jurisdictions in which they operate around the world"--